2022
DOI: 10.1177/17470218221141644
|View full text |Cite
|
Sign up to set email alerts
|

Absence of age differences in emotion perception and gaze patterns using a contextually rich film-based assessment

Abstract: Age differences in emotion perception are now well documented. However, a key limitation of many studies in this literature is the reliance on highly artificial tasks that lack context and consequently have poor ecological validity. This study reports two separate experiments that investigated age differences in emotion perception abilities using a highly contextualised film-based assessment along with a traditional emotion perception task. Experiment 2 additionally included a middle-aged sample and an assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…This finding aligns with broader literature showing ecologically valid stimuli appear to enhance older adults’ performance on tasks spanning several subcomponents of social cognition (see Blanke & Riediger, 2019, for a review). For example, previous research has found that enhancing stimuli ecological validity in emotion recognition tasks improves performance for older adults and reduces age effects (e.g., Grainger & Henry, 2022; Richter et al, 2011; Stanley & Isaacowitz, 2015; Wieck & Kunzmann, 2017). Overall, then, the present study aligns with extant literature which has demonstrated that ecological validity is not only an important factor in any consideration of age effects in social cognition but also meaningfully extends this literature by showing, for the first time, that this is the case for gaze following.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with broader literature showing ecologically valid stimuli appear to enhance older adults’ performance on tasks spanning several subcomponents of social cognition (see Blanke & Riediger, 2019, for a review). For example, previous research has found that enhancing stimuli ecological validity in emotion recognition tasks improves performance for older adults and reduces age effects (e.g., Grainger & Henry, 2022; Richter et al, 2011; Stanley & Isaacowitz, 2015; Wieck & Kunzmann, 2017). Overall, then, the present study aligns with extant literature which has demonstrated that ecological validity is not only an important factor in any consideration of age effects in social cognition but also meaningfully extends this literature by showing, for the first time, that this is the case for gaze following.…”
Section: Discussionmentioning
confidence: 99%